HUBUNGAN ANTARA PARTISIPASI DALAM PENGEMBANGAN SISTEM INFORMASI DENGAN PERKEMBANGAN PENGGUNAAN TEKNOLOGI INFORMASI (SUATU TINJAUAN DENGAN DUA FAKTOR KONTIJENSI) - Amrul, Sadat (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2004)
This study empirically examined the influence of two contingency factors: involvement executive and system complexity on the relationship between user participation and progressive use of information technology in Indonesian's Banking Industry, with residual approach. This approach is used to avoid econometrics problem which often arise at usage of interaction method in regression analysis using contingency factors.Based on respons 92 managers, result of this research indicate that relation between executive participation in development of information system with progressive use information technology positive and signifikan, result of this similar with theoretical base that active participation of executive in development of information system improve progressive use of information technology. Second, the results study indicated that factor executive involvement in development of information system have an effect on significan so that strengthen direct relation between participation with progressive use information technology. Combination according to betweenparticipation involvement executive (high) can improve progressive use of realized information technology with direct role of executive to innovation and successfulness use of information technology. While result of research concerning influence of system complexity to relation between executive participation in development of information technology with progressive use of information technology do not obtain evidence support which significan, that system complexity strengthen the relation.